PREVALENCIA DE ENFERMEDADES DE IMPACTO REPRODUCTIVO EN BOVINOS DE LA ESTACIÓN EXPERIMENTAL DE TRÓPICO DEL CENTRO DE INVESTIGACIONES IVITA - Rivera G., Hermelinda (2004)
The prevalence of infectious agents associated with reproductive failures in Zebu and crossbred cattle (n=268), older than six months of age, from the IVITA Research Center herd in Pucallpa, Peru, was determined. Serum samples were collected for the detection of antibodies against Brucella sp., Leptospira serovares: canicola, icterohemorrhagiae, pomona and hardjo, Bovine Viral Diarrhea Virus (BVDV), Bovine Herpes Virus Type 1 (BHV-1) and Neospora caninum by a commercial indirect ELISA, microglutination, viral neutralization and indirect immunofluorescence tests, respectively. No antibodies were detected against Brucella sp., L. pomona and BVDV. The 46.3 ± 6.0% of the animals had antibodies against BHV-1. The highest seroprevalence of BHV-1 (63.2%) was found in cows older than 18 months. Antibody titres against BHV-1 varied from 2 till >256. The 52.2% of the animals had antibodies against Leptospira. The higher prevalence (35%) corresponded to L. hardjo followed by L. canicola and L. icterohemorrhagiae (14.9%). The titers of antibodies ranged from 1:100 to 1:400. Antibodies against N. caninum was found in 1.5% of the samples. These results indicate that Brucella sp. and BVDV are not prevalent in the herd. The eradication of N. caninum is feasible due to its low prevalence, but BHV-1 and Leptospira could be considered of sanitary risk for this herd.